Answer:
1/6
Step-by-step explanation:
Answer:
24
Step-by-step explanation:
1/2(x1+x2)c x1=3 , x2=5 , c=6
:- 1/2(3+5)6 ( BODMAS)
:- 1/2(8)6 divide 8 by 1/2
:- (4)6 multiply both of them and the result = 24
Answer:
9/20
Step-by-step explanation:
I guess I was help full for u
plz follow me for more updates
Answer:
x=(8/3, infinity)
Step-by-step explanation:
-3x+8<15-3x+8
-3x+8<-3x+23
8<23
15-3x+8<15
23-3x<15
-3x<-8
x>8/3
Therefore, x=(8/3, infinity)
Formula for growth:
y = initial • (percent growth + 1)^time/frequency of growth
So, since initial population is 382
Percent growth is 0.007
The time is 30 years
And it goes it by .07% every 1 year,
y = 382 • (1.007)^30/1
y= 470.9203732 people
Since we can’t have 0.9 of a person, the population after 30 years will be 470 people.